Evaluation of the supplementary recovery feeding program (PMT-P) on the improvement of nutritional status among stunted children under five in Depok Village, Batang Regency - Nazza Aulia; Eva Dwijayanti; Aurora Clarinta Ana Purwanto; Zarifah Dwi Iriani; Zahran Nafaza; Teguh Irawan; Yulis Indriyanti (Indonesian Journal of Health Science, 2026)
Stunting is a long-term growth problem in toddlers caused by malnutrition and requires immediate treatment. One of the main ways to address this problem is through the Supplementary Feeding Recovery (PMT-P) program that uses local food ingredients. This study aims to assess the effectiveness of the PMT-P program in improving the nutritional status of stunted toddlers in Depok Village, Batang Regency, using an input, process, and output approach. This study applied a qualitative method with data collection through in-depth interviews and field observations conducted from April to May 2026. A total of 13 informants were involved, consisting of nutrition program managers, village midwives, village officials, integrated health post (Posyandu) cadres, and mothers of toddlers as sources of triangulation information. The authenticity of the data was tested through source triangulation, then analyzed using descriptive narrative. The results of the evaluation of the input and process components indicate that the availability of cadres, technical competence, and budget collaboration have contributed to program implementation, despite limitations in nutrition education media and animal protein menu variations due to logistical problems with storing fresh ingredients. However, the output and impact components of the program showed positive results, where all recorded stunted toddlers were successfully reached by the PMT-P intervention. In addition, most mothers of toddlers reported that their children were obedient and finished the additional food portions provided regularly. This intervention successfully provided a real positive impact, namely a gradual increase in toddlers' weight. Informants, including village midwives and cadres, perceived changes in the physical condition and improvements in toddlers' weight quite well during the program, in line with the focus of this study which examined the depth of the program implementation process in the field. Thus, it can be concluded that the implementation of the PMT-P program in Depok Village has generally run well in both input and process components, and is perceived to provide positive physical changes in toddlers, although the management of the supply of varied menus and the availability of educational facilities need to be further improved.